Stunting in Indonesia: Current progress and future directions - Vernando Yanry Lameky (Belitung Raya Foundation, 2024)
This narrative review article aims to describe the issue of stunting in Indonesia, a condition from chronic malnutrition that impairs children's growth and development. With a stunting prevalence of approximately 30% among children under five, this problem is a critical concern for policymakers and healthcare providers. The article also reviews various interventions, including programs to enhance nutrition, promote breastfeeding, and improve sanitation. By assessing these existing interventions, health policy strategies and service management enhancements are proposed to reduce stunting rates. It underlines the necessity of a comprehensive approach integrating cross-sector collaboration and community engagement to achieve lasting solutions. The insights provided are crucial for policymakers to refine and enhance intervention strategies, aiming to lessen the long-term health impacts and improve children's well-being in Indonesia.